2016
DOI: 10.1117/1.jmi.3.1.019801
|View full text |Cite
|
Sign up to set email alerts
|

Superficial vessel reconstruction with a Multiview camera system

Abstract: Abstract. We aim at reconstructing superficial vessels of the brain. Ultimately, they will serve to guide the deformation methods to compensate for the brain shift. A pipeline for three-dimensional (3-D) vessel reconstruction using three mono-complementary metal-oxide semiconductor cameras has been developed. Vessel centerlines are manually selected in the images. Using the properties of the Hessian matrix, the centerline points are assigned direction information. For correspondence matching, a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In [8] brain displacements are estimated by manually defining vessel centerlines and then using them to drive a Coherent Point Drift matching algorithm to register preoperative MRI scans. This method was later improved to extract vessel centerlines from multiview cameras and reconstruct their 3D shape [9]. Using an optically tracked stylus Luo et al [10] manually identified cortical vessel features to estimate brain shift and corrected it for after dural opening using a model-based registration.…”
Section: Introductionmentioning
confidence: 99%
“…In [8] brain displacements are estimated by manually defining vessel centerlines and then using them to drive a Coherent Point Drift matching algorithm to register preoperative MRI scans. This method was later improved to extract vessel centerlines from multiview cameras and reconstruct their 3D shape [9]. Using an optically tracked stylus Luo et al [10] manually identified cortical vessel features to estimate brain shift and corrected it for after dural opening using a model-based registration.…”
Section: Introductionmentioning
confidence: 99%
“…Stereo camera systems represent an effective instrument for 3D reconstruction in great variety of applications and in different fields of science, entertainment, industry and automotive, [1], [2], [3], [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…I N recent years technological advances in the field of imaging and computer vision, together with the growing demand for 3D contents, contributed to make digital camera stereo systems accurate in the 3D reconstruction and at the same time accessible to a wide audience. This led to the proliferation of stereo vision applications in fields as diverse as entertainment [1]- [3], surveillance [4]- [7], navigation [8]- [11], robotics [12]- [15], medicine [16]- [19] and biology [20]- [23].…”
Section: Introductionmentioning
confidence: 99%